Morphofunctional patterns of thymus and mediastinal lymph node reactivity after intrauterine administration of staphylococcal toxoid in the early postnatal period in the experiment - Kushch , O.G.; Holovatskyi , A.S. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. Recent years have been characterized by an increase in the incidence of infectious and allergic diseases. The aim of the study was to establish the patterns of morphofunctional restructuring of the primary lymphoid organ (thymus) and secondary mediastinal lymph node after intrauterine administration of staphylococcal anatoxin. Methods. Histological examination – light microscopy. The cellular composition of the mediastinal lymph nodes and thymus was studied under a microscope. The results were processed using statistical methods. Results. Intrauterine exposure to staphylococcal anatoxin leads to increased thymus lymphocyte proliferation during the early postnatal period. This is accompanied by changes in intra-thymic migration processes, accompanied by disorganization of positive and negative selection processes, leading to increased lymphocyte emigration from the organ to the periphery. Among these lymphocytes, there may be autoreactive clones, the release of which can lead to a breakdown of central tolerance. Intrauterine administration of staphylococcal anatoxin leads to a progressive increase in the number of lymphocytes. The results of the studies complement existing ideas about the mechanisms of intrauterine antigenic influence on the formation of the immunological status of newborns in the early period of ontogenesis. With its unique topography and against the backdrop of altered thymus morphogenesis, after intrauterine exposure to staphylococcal anatoxin, the structure of the mediastinal lymph node fully reproduces the reactive changes of all links of immunity, which allows predicting changes in the initial immunity of newborns with a complicated prenatal diagnosis. Conclusions. 1. Intrauterine exposure to staphylococcal anatoxin leads to an increase in the intensity of lymphocyte proliferation in the thymus parenchyma. This leads to changes in the processes of intratymic migration, accompanied by the disorganization of positive and negative selection processes, which leads to an increase in the proportion of lymphocytes capable of migrating from the organ to the periphery. Among these lymphocytes, there may be autoreactive clones, the release of which can lead to a breakdown of central tolerance. 2. Intrauterine administration of staphylococcal anatoxin leads to a progressive increase in the number of lymphocytes. Such changes can lead to increased reactivity of the secondary lymphoid organ, which can manifest itself in various allergic conditions.